Effect of Soil Covering on the Soil Enzyme Activity of Integrated Orchard - Varga, Csaba; Helmeczi, Balázs (Acta Agraria Debreceniensis, 2004)
The purpose of our experiments is to discover the effect of different soil cover matters (agrofoil and black polyethylene) on the activity of some enzymes (phosphatase, saccharase, urease, catalase, dehydrogenase) occuring in soil. Soil samples were taken from a cider apple plantation of the Fruit Producing Research and Advisory Kht Újfehértó. The enzyme activity was measured according to Krámer and Erdei (1959a), Kuprevič and Tsherbakova (1956), Kuprevič et al. (1966), Frankenberger and Johanson (1983), Mersi and Schinner (1991). Soil moisture content was by conventional (drying chamber) method measured during every sampling and enzyme activity was transpolated to absolute dry soil. Results were estimated by mathematical methods (variation analysis, correlation counting). Soil samples were taken by trials 5 times (in every two months) a year in the vegetation period from March to November. By recording the monthly changes of the enzyme activity we have observed the following. The activity of the phosphatase was generally the highest in May and the lowest in November. Depending on the trials, high values were also measured in March and September. The activity of the saccharase was generally the highest in November and the lowest in June, but at the same time peaks even occured in May and September. The highest urease avtivity was measured in September and November, and the lowest activity in May and July, also depending on the trials. In the year 2000, after a deep point in March, the activity of the catalase was the highest in November or by certain trials in September. In 2001, the lowest activity was also measured in March, but the highest activity appeared in November in case of one-minute trial, and in May in consequence of two-minute trial. Finally the activity of dehydrogenase was the highest in November and the lowest in July apart from the model years. There were essential differences in rainfall of the two experimental years which was reflected in the enzyme activities. There was a poor positive significant relationship between soil moisture content and enzyme activity values in case of phosphatase, saccharase, urease (r=0,426; 0,480; 0,396) respectively. In case of catalase1 (r=0,518), catalase (r=0,556), dehydrogenase (r=0,559) we obtained a medium strong positive relationship between soil moisture content and enzyme activity values. By evaluating the effect of different trials in case of every examined enzyme significantly higher values were detected in soils covered by agrofoil (a porous black polyethylene) than in soils covered by black polyethylene or in uncovered soils. Moreover, the soil covered by black polyethylene showed significantly higher enzyme activities (besides phosphatase) than the control soil. Thus soil-covering meant statistically significant advantages in enzyme activity as opposed to uncovered soil proved.